2023
DOI: 10.1093/stcltm/szad007
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Based Regimen Rescues Endometrial Fibrosis in Intrauterine Adhesions Via Targeting Clinical Fibrosis Biomarkers

Abstract: Intrauterine adhesions (IUA), which is characterized by endometrial fibrosis, continue to be the most common cause of uterine infertility globally. Our work revealed that 3 fibrotic progression markers (Vimentin, COL5A2, and COL1A1) were significantly increased in the endometrium of IUA patients. Mesenchymal stem cell–derived exosomes (EXOs) have been recently revealed as a cell-free therapy for fibrosis diseases. Nevertheless, the application of EXOs is restricted by the short residency duration in the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Furthermore, compared with that in the uterine injury group, we observed increased expression of the endometrial stromal cell marker vimentin in the UC-MSC+hydrogel group, hydrogel group and UC-MSC group, which were close to the result in the blank group, indicating improved endometrial regeneration in the rats ( Figures S2 I and S2J; uterine injury vs. hydrogel vs. UC-MSC vs. UC-MSC+hydrogel vs. blank; 76.5 ± 40.0 vs. 114.1 ± 18.4 vs. 110.0 ± 13.9 vs. 123.9 ± 12.4 vs. 128.1 ± 11.6, respectively). 5 , 34 , 35 , 36 , 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, compared with that in the uterine injury group, we observed increased expression of the endometrial stromal cell marker vimentin in the UC-MSC+hydrogel group, hydrogel group and UC-MSC group, which were close to the result in the blank group, indicating improved endometrial regeneration in the rats ( Figures S2 I and S2J; uterine injury vs. hydrogel vs. UC-MSC vs. UC-MSC+hydrogel vs. blank; 76.5 ± 40.0 vs. 114.1 ± 18.4 vs. 110.0 ± 13.9 vs. 123.9 ± 12.4 vs. 128.1 ± 11.6, respectively). 5 , 34 , 35 , 36 , 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the endometrial morphology indicated significant recovery of the uterine injury in the rat model treated with hydrogel-loaded UC-MSCs, accompanied by a notable reduction in fibrosis and successful restoration of the regenerative capacity within the endometrium. 1 , 5 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…Studies show that the application of thermosensitive hydrogels reduces endometrial injury. [66] To further improve the therapeutic efficacy, we developed injectable thermosensitive hydrogels (CS/GP) capable of encapsulating TSG6-modified Exos (TSG6-Exo@CS/GP). This innovative approach enabled targeted delivery of TSG6-modified-Exos to the uterine cavity, ensuring sustained release and timely administration.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in exosome functionality and stability across different samples and storage conditions necessitates further research for clinical application. Establishing standardized and scalable production processes is imperative for consistent and replicable exosome-based therapies [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%